Antidiabetic and Synergistic Effects Study of Anthocyanin Fraction from Berberis integerrima Fruit on Streptozotocin-Induced Diabetic Rats Model - Zahra Sabahi; Mohammad Javad Khoshnood-Mansoorkhani; Solmaz Rahmani Namadi; Mahmoodreza Moein (Shiraz University of Medical Sciences, 2016)
Introduction: Diabetes mellitus is a complex endocrine disorder. There is serious attempt to realize antidiabetic compound from natural sources to use with other drugs for reduction of diabetes complication.  Materials and Methods: Present study is based on the investigation of antihyperglycemic effect of anthocyanin fraction of Berberis integerrima (AFBI) fruits on some physiological parameters (glucose level, glycogen content and body weight) in normal and streptozotocin-induced (STZ-induced) diabetic rats and evaluation of synergic effect of this fraction with metformin and glybenclamid. Male Sprague dawley rat were divided into nine groups: healthy control group, diabetic control group, diabetic groups treated with anthocyanin fraction (200, 400 and 1000 mg/kg, respectively); diabetic groups treated with glybenclamide and metformin separately, diabetic groups treated with glybenclamide + anthocyanin fraction (1000 mg/kg), metformin +anthocyanin fraction (1000 mg/kg).  Results: Treatment of diabetic rats with AFBI (400, 1000mg/kg) significantly decreased blood glucose as compared with control. Moreover AFBI (400, 1000mg/kg) significantly increased liver glycogen and body weight in compared to control. Nevertheless there were no synergistic effects between anthocyanin fraction and metformin or glibenclamid on blood glucose, liver glycogen and body weight. Conclusion: The results of this study indicate that AFBI possesses hypoglycemic effects and may be considered for evaluation in future diabetes clinical studies.